Increased nm23 immunoreactivity is associated with selective inhibition of systemic tumour cell dissemination. Issue 3 (1st March 2002) - Graham, A N J; Maxwell, P; Mulholland, K; Patterson, A H; Anderson, N; McManus, K G; Bharucha, H; McGuigan, J A
Abstract : Aims: In vitro transfection experiments show that the nm23 gene suppresses metastasis, although the evidence from clinical studies is contradictory. The purpose of this study was to investigate whether nm23 selectively influences systemic, pleural, and lymphatic metastasis in non-small cell lung cancer (NSCLC). Methods: Forty two patients undergoing resection of NSCLC and lymph node sampling were enrolled prospectively. In each case, a bone marrow aspirate, pleural lavage, and lymph nodes were assessed using immunohistochemistry for epithelial antigens and morphology. The intensity of nm23-H1 immunoreactivity of the primary tumour was compared with the internal control of normal bronchial epithelium in 32 cases where available. The microvessel count (MVC) of each tumour was determined using immunohistochemistry for the endothelial cell marker CD34. Results: Tumour cell dissemination was detected in the bone marrow in 18 patients, in the pleura in seven, and in the lymph nodes in 21. Increased immunoreactivity for nm23 was found in the primary tumour in six patients, with none having tumour cells in the bone marrow, compared with 12 of 26 patients who showed nm23 immunoreactivity equal to or less than the control (Fisher's exact test: p = 0.043). This effect was confirmed to be independent of the MVC on multivariate analysis. There was no significant difference in the incidence of pleural or lymphatic tumour cell dissemination between the two groups. Conclusions: nm23 appears to be a suppresser of systemic, but not lymphatic, metastasis in primary NSCLC.